Seasonal variation of river and tide energy in the Yangtze estuary, China. Issue 1 (28th August 2015) - Zhang, Min; Townend, Ian; Zhou, Yunxuan; Cai, Huayang
Abstract: In many large estuaries there are significant variations in flow conditions due to the interaction between tide (with spring–neap changes) and river discharge (with wet–dry seasons), which is key to understanding the evolution of the morphology and the resultant equilibrium state. To explore whether there exists an equilibrium state, and what might control such a state in such a dynamic environment, both numerical and analytical methods have been used to investigate the relative importance of tide and river contributions to the work done locally and globally over a wide range of discharge conditions in the Yangtze estuary. In particular, we have quantified the contributions from the tidal flow, the river flow and the tide–river interaction in terms of energy and its dissipation under different river discharge conditions. Model results suggest that there is a state of minimum tidal work for the case representing the wet season, when river and tide are doing uniform work locally and minimum work globally, within the bi‐directional tidal reach for tide and along the whole estuary for river. We also observe that the system is not optimized for other conditions (peak discharge and low flows during the dry season), but the system would tend to do the minimum work possible given the constraints on the system (e.g. imposed forcing conditions and available sediment supply). Results, therefore, are consistent with the use of these two energetic optimization principles, and the proposed method could be applicable to other alluvial estuaries. Copyright © 2015 John Wiley & Sons, Ltd.